Protection against influenza-induced Acute Lung Injury (ALI) by enhanced induction of M2a macrophages: possible role of PPARγ/RXR ligands in IL-4-induced M2a macrophage differentiation - Gopalakrishnan, Archana; Joseph, John; Shirey, Kari Ann; Keegan, Achsah D.; Boukhvalova, Marina S.; Vogel, Stefanie N.; Blanco, Jorge C. G. (Frontiers in Immunology, 2022)
Many respiratory viruses cause lung damage that may evolve into acute lung injury (ALI), a cytokine storm, acute respiratory distress syndrome, and ultimately, death. Peroxisome proliferator activated receptor gamma (PPARγ), a member of the nuclear hormone receptor (NHR) family of transcription factors, regulates transcription by forming heterodimers with another NHR family member, Retinoid X Receptor (RXR). Each component of the heterodimer binds specific ligands that modify transcriptional capacity of the entire heterodimer by recruiting different co-activators/co-repressors. However, the role of PPARγ/RXR ligands in the context of influenza infection is not well understood. PPARγ is associated with macrophage differentiation to an anti-inflammatory M2 state. We show that mice lacking the IL-4Rα receptor, required for M2a macrophage differentiation, are more susceptible to mouse-adapted influenza (A/PR/8/34; “PR8”)-induced lethality. Mice lacking Ptgs2, that encodes COX-2, a key proinflammatory M1 macrophage mediator, are more resistant. Blocking the receptor for COX-2-induced Prostaglandin E2 (PGE2) was also protective. Treatment with pioglitazone (PGZ), a PPARγ ligand, increased survival from PR8 infection, decreased M1 macrophage gene expression, and increased PPARγ mRNA in lungs. Conversely, conditional knockout mice expressing PPARγ-deficient macrophages were significantly more sensitive to PR8-induced lethality. These findings were extended in cotton rats: PGZ blunted lung inflammation and M1 cytokine gene expression after challenge with non-adapted human influenza. To study mechanisms by which PPARγ/RXR transcription factors induce canonical M2a genes, WT mouse macrophages were treated with IL-4 in the absence or presence of rosiglitazone (RGZ; PPARγ ligand), LG100754 (LG; RXR ligand), or both. IL-4 dose-dependently induced M2a genes Arg1, Mrc1, Chil3, and Retnla. Treatment of macrophages with IL-4 and RGZ and/or LG differentially affected induction of Arg1 and Mrc1 vs. Chil3 and Retnla gene expression. In PPARγ-deficient macrophages, IL-4 alone failed to induce Arg1 and Mrc1 gene expression; however, concurrent treatment with LG or RGZ + LG enhanced IL-4-induced Arg1 and Mrc1 expression, but to a lower level than in WT macrophages, findings confirmed in the murine alveolar macrophage cell line, MH-S. These findings support a model in which PPARγ/RXR heterodimers control IL-4-induced M2a differentiation, and suggest that PPARγ/RXR agonists should be considered as important tools for clinical intervention against influenza-induced ALI.